Aspects Of Characterizations From The Characters In 'Cruella' Movie - Dewi, Gelia Asari; I Dewa Ayu Devi Maharani Santika; I G B Wahyu Nugraha Putra (Journal of Language and Applied Linguistics, 2025)
Characterization is the way that can be used to analyze characters in a movie. This study raises two problems, namely what the types of characters and how is the characterization of the characters from Cruella movie. The theory is taken from Tarigan (1985) and Warren and Wellek (1962). The data source of this research was the movie Cruella by Craig Gillespie. The data were collected through qualitative research method. Observation and note taking are used to collect the data. The result shows that there are 12 characters appear in the movie. Most of the characters have complete aspects of characterization, those are physiological aspect, psychological aspect and sociological aspect. The rest of them only have one or two aspects because they are as supporting characters who appear only several times in the movie.